Analysis of the role of cadres and mothers’ motivation in improving coverage of vitamin a capsule administration for toddlers - Hayu, Ramah; Darma, Ika Yulia; Fransisca, Dewi; Dewi, Ratna Indah Sari (Science Midwifery, 2024)
According to the World Health Organization (WHO) in 2021 vitamin A deficiency is one of the highest causes of blindness in the world with an estimated 250,000-500,000 children losing their every years. The national coverage of giving vitamin A capsules for toddlers under five reached 90.2%, still below the national target of 100%. The population of parents who have children under five come to visited Dadok Tunggul Hitam Padang Health Center in the last 3 months 268 people and the sample size is 72. Accidental sampling technique. The results showed that more than half (53.8%) of the participants did not get vitamin A capsules. More than half (52.5%) of respondents had poor motivation about vitamin A capsules in children under five. Less than half (37.5%) of respondents have posyandu cadres do not play a role about giving vitamin A capsules to children under five. There is a link between motivation and the role of posyandu cadres with the provision of vitamin A capsules in children under five.